Cavern Boundary Determination with Pseudoplastic Fluid Based on the Apparent Viscosity Method. Issue 9 (3rd June 2020) - Luan, Deyu; Chen, Yiming; Wang, Hong; Wang, Zhaorui; Wang, Songsong; Li, Longbin
Abstract: The cavern characteristics of xanthan gum solutions stirred by impellers of a perturbed six‐bent‐bladed turbine (6PBT) were investigated numerically using computational fluid dynamics (CFD) with laminar flow model. The apparent viscosity method was proposed to determine the boundary of the cavern. The cavern sizes predicted by apparent viscosity were in good agreement with the calculated results, and this method was not influenced by speed and impeller configuration. However, the predicted results of the cavern by the traditional speed method usually displayed a great deviation, especially at high speed. Therefore, it is feasible to determine the cavern boundary with the apparent viscosity, i.e., 0.25 times the yield viscosity of a pseudoplastic fluid, as the unified standard. Abstract : Cavern formations of xanthan gum solutions with different mass fractions stirred by impellers of a perturbed six‐bent‐bladed turbine were investigated numerically by computational fluid dynamics with laminar flow model. The apparent viscosity method is suggested for determination of the cavern boundary and was more accurate for evaluating cavern shapes than the traditional velocity method.